Amisulpride Augmentation for Clozapine-Refractory Positive Symptoms: Additional Benefit in Reducing Hypersialorrhea. (9th March 2015) - Bogorni, Fabiani; Moreira, Frederico Fernandes; Pimentel, Eduardo Mylius; Grohs, Géder Evandro Motta; Diaz, Alexandre Paim
Abstract : One-third to half of patients taking clozapine suffer from refractory symptoms despite adequate treatment. Among other adverse effects, clozapine-induced hypersalivation (CIH) occurs in approximately half of all patients. This is a case of a 30-year-old male with refractory schizophrenia; in this patient, the remission of residual positive symptoms, as well as the reduction of CIH, was achieved by treatment with clozapine augmented with amisulpride.